What Is the Heritability of Periodontitis? A Systematic Review - Nibali, L.; Bayliss-Chapman, J.; Almofareh, S.A.; Zhou, Y.; Divaris, K.; Vieira, A.R. (Journal of dental research, 2019)
The aim of this study was to systematically appraise the existing literature on the yet-unclear heritability of gingivitis and periodontitis. This review was conducted following the PRISMA guidelines. A search was conducted through the electronic databases Medline, Embase, LILACS, Cochrane Library, Open Grey, Google Scholar, and Research Gate, as complemented by a hand search, for human studies reporting measures of heritability of gingivitis and periodontitis. A total of 9,037 papers were initially identified from combined databases and 10,810 on Google Scholar. After full-text reading, 28 articles met the inclusion criteria and were carried forward to data abstraction. The reviewed data included information from >50,000 human subjects. Meta-analyses were performed by grouping studies based on design and outcome. Heritability (H2) of periodontitis was estimated at 0.38 (95% CI, 0.34 to 0.43; I2 = 12.9%) in twin studies, 0.15 (95% CI, 0.06 to 0.24; I2 = 0%) in other family studies, and 0.29 (95% CI, 0.21 to 0.38; I2 = 61.2%) when twin and other family studies were combined. Genome-wide association studies detected a lower heritability estimate of 0.07 (95% CI, −0.02 to 0.15) for combined definitions of periodontitis, increasing with disease severity and when the interaction with smoking was included. Furthermore, heritability tended to be lower among older age groups. Heritability for the self-reported gingivitis trait was estimated at 0.29 (95% CI, 0.22 to 0.36; I2 = 37.6%), while it was not statistically significant for clinically measured gingivitis. This systematic review brings forward summary evidence to confirm that up to a third of the periodontitis variance in the population is due to genetic factors. This seems consistent across the different studied populations and increases with disease severity. In summary, up to a third of the variance of periodontitis in the population is due to genetic factors, with higher heritability for more severe disease.